Event-Triggered Control for Network-Based Switched Systems With Switching Signals Subject to Dual-Terminal DoS Attacks - Qi, Yiwen; Yu, Wenke; Zhao, Xudong; Xu, Xindi (IEEE/ACM transactions on networking, 2022)
This paper investigates event-triggered control for saturated switched systems with switching signals subject to dual-terminal denial-of-service (DoS) attacks. The original switching signals are sampled and transmitted to sub-system and sub-controller through networks, respectively. However, the openness of network may cause switching signal transmission to be affected by possible DoS attacks. Moreover, the existing dual-terminal mismatched network delays and attacks could lead to asynchronous phenomenon. Considering the impacts of the attacked switching signals and delays, a time-delay closed-loop switched system is developed. Subsequently, by utilizing piecewise Lyapunov functional technique, various cases caused by DoS attacks and different delays are analyzed. Then, novel conditions are derived to ensure the stability of closed-loop switched system, and sufficient conditions for the desired controller gains and event-triggering parameters are presented. Finally, simulation examples are given to verify the effectiveness of the proposed method. The simulation results show that in the case of single-terminal and dual-terminal attacks, switched systems both have good anti-attack characteristics.